Penyuluhan Hukum Tentang Perlindungan Hak-Hak Perempuan Di Desa Rumberu Kecamatan Inamosol Kabupaten Seram Bagian Barat - Mahrita Aprilya Lakburlawal; Jenny Kristiana Matuankotta; Novyta Uktolseja; Primus L Untajana (Faculty of Law Pattimura University, 2021)
Introduction: women are always seen as second-class beings who are weak, irrational and do not have the ability to even make decisions for their own interests, resulting in the neglect of women's rights which causes low levels of education, early marriage, restrictions on activities in these sectors. and violence are problems experienced by women in the village.Purposes of Devotion: Purpose of the Reaserch: to provide an understanding regarding the protection of women's rights in the hope that there will be an understanding regarding the equality of the position of women and men as well as more opportunities for women to be involved in development in Rumberu village. Method of Devotion: Counseling is carried out using the panel discussion method which begins with a lecture from each presenter in turn, followed by a questions and answers session between the presenters and the community.Results of the Devotion: Women in Rumberu village, Inamosol District, West Seram Regency, like women in other regions in Indonesia, have had their rights violated in various ways. Women in Rumberu village experience various injustices because of their existence as women such as marginalization/marginage, subordination, stereotypes, violence and double workload. Among them, violence is the most common problem in Rumberu village. this is due to the low level of education and economy, lack of understanding of women's rights, as well as the prevailing customs and culture in Rumberu Country. Even though women are potential development capital, there needs to be an understanding of the position of women so that there is equality.